Chapter V: Maxima and Minima (Quarterly Journal of Economics, 1938)
Chapter V: Maxima and Minima Get access The Quarterly Journal of Economics, Volume 52, Issue Supplement, May 1938, Pages 117–139, https://doi.org/10.1093/qje/52.Supplement.117 Published: 01 May 1938